A STUDY ON DEVELOPING THERMO-REGULATING DENIM FABRIC BY INTEGRATING OF MICROENCAPSULATED PHASE CHANGE MATERIAL USING EXHAUSTION METHOD - ÖNER Erhan (Annals of the University of Oradea: Fascicle of Textiles, Leatherwork, 2019)
A blend of octadecane and organic coconut oil were used as phase change material in core and melamine formaldehyde was used in shell to produce microencapsulated thermal storing material. A melamine resin containing methylol was used as crosslinker for the polymer shell. The microencapsulation was processed using in-situ polymerization method. The synthesized microcapsules (microPCM) were applied to a stretch denim fabric with composition of 98 % cotton and 2% elastane, which is widely used in daily life as jeanswear, by using exhaustion method in different concentrations. The core material, the microcapsule and the treated fabrics were analyzed by Fourier Transform Infrared Spectroscopy (FT-IR), Differential Scanning Calorimetry (DSC) and Scanning Electron Microscopy (SEM). FT-IR results revealed that the microcapsules were fabricated successfully. SEM images indicated that the microcapsules were yielded in spherical form with a particle size of 1-3 µm. and the particles were achieved to be exhausted in the fabric texture, comparing to untreated fabric. DSC results showed that the microcapsules stored latent heat of melting 111 J/g at a peak temperature of 28.1ºC and the treated fabrics possessed latent heat of melting 0.7-0.8 J/g at peak temperatures of 25.2-25.5 ºC which are in human comfort temperature range. It was calculated that the microcapsules were obtained with a 70.3% encapsulation yield in 63.4 % core content.